Pengukuran Persepsi Pengguna Terhadap Persepsi Manfaat, Fitur Layanan Dan Keamanan Mobile Banking (Studi Kasus Pada Nasabah BRI Wilayah Ciayumajakuning) - Budi Rusdian; Rita Kusumadewi (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
This research aims to examine the influence of perceived benefits, service features and security of the BRImo application on PT customers. Bank Rakyat Indonesia (Persero) Tbk. The research was conducted using an online questionnaire to BRImo user customers in the Ciayumajakuning area. This research used quantitative descriptive research with a total of 100 respondents and questionnaires were distributed using the Google Form application. The results of this research show that perceived benefits, service features and security have a positive effect on attitudes towards using the BRImo application.